Efficacy and Safety of Drug-Eluting Bead TACE in the Treatment of Primary or Secondary Liver Cancer - Jiabing Wang; Haoqian Xu; Ying Wang; Long Feng; Fengming Yi (Canadian Journal of Gastroenterology and Hepatology)
Background. The drug-eluting beads transarterial chemoembolization (DEB-TACE) has already been used in hepatic malignancies. We aim to evaluate the efficacy and safety of DEB-TACE in treating primary or secondary liver cancer. Methods. We retrospectively evaluated 59 patients with hepatic malignancies, including 41 patients with primary liver cancer and 18 patients with secondary liver cancer, between September 2016 and February 2019. All patients were treated with DEB-TACE. Objective response rate (ORR) and disease control rate (DCR) were evaluated by mRECIST. The pain was assessed using a numerical rating scale (NRS) where 0 represented no pain, and a score of ten was unbearable. Adverse reactions were assessed according to Common Terminology Criteria for Adverse Events 4.0 (CTCAE4.0). Results. In the subgroup of primary liver cancer, 3 patients (7.32%) got complete response, 13 patients (31.71%) got partial response, 21 patients (51.22%) experienced stable disease, and 4 patients (9.76%) suffered progressive disease; ORR was 39.02% and DCR was 90.24%. In the subgroup of secondary liver cancer, 0 patients (0%) got complete response, 6 patients (33.33%) got partial response, 11 patients (61.11%) experienced stable disease, and 1 patient (5.56%) suffered progressive disease; ORR was 33.33% and DCR was 94.44%. We did not find any difference when comparing the efficacy between primary and secondary liver cancer (P=0.612). The one-year survival rate was 70.73% for primary liver cancer and 61.11% for secondary liver cancer. There was no significant difference between the two groups (P=0.52). For the patients with CR or PR, no factor could predict the efficacy of DEB-TACE. The most common treatment-related adverse reactions were short-term liver function disorders. The symptoms included fever (20.34%), abdomen pain (16.95%), and vomiting (5.08%), all patients with adverse reactions got remission after treatment. Conclusions. DEB-TACE has a promising effect in the treatment of primary or secondary liver cancer. The treatment-related adverse reactions are tolerable.